Contemporary Uzbek Modern Literature And The Impact Of Eliot’s Works On It (Eurasian Journal of Humanities and Social Sciences, 2026)
This article explores the influence of T. S. Eliot on contemporary Uzbek modern literature. The study aims to analyze how Eliot’s poetic techniques, modernist philosophy, and literary innovations have contributed to the development of Uzbek poetic expression and critical thought. Using comparative literary analysis, the research examines intertextual connections, stylistic adaptation, and thematic similarities between Eliot’s works and selected examples of Uzbek modern poetry. The findings indicate that Eliot’s influence is visible in the use of fragmented structure, symbolism, philosophical reflection, and modernist aesthetics in Uzbek literary discourse. The article concludes that Eliot’s works have played an important role in shaping modern literary consciousness in Uzbekistan, particularly in the areas of poetic form and intellectual depth.